Integrasi Perangkat Web Interaktif dalam Pembelajaran Tematik Anak Usia Dini: Studi Deskriptif Kualitatif di PAUD Ponorogo - Nur Fahmi, Muhammad; Syapon, Syapon; Kartikasari, Riska; Agustina, Eka; Dwi Laksana, Sigit (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
The integration of technology in early childhood education represents a strategic response to the challenges of 21st-century learning, particularly within the Merdeka Belajar (Independent Learning) era that emphasizes institutional innovation and autonomy. This study aims to describe the implementation of interactive web-based tools in thematic learning for early childhood in Ponorogo, Indonesia. A descriptive qualitative approach was employed, involving teachers and students as participants. Data were collected through observations, interviews, and documentation, and analyzed thematically. The findings reveal that (1) the use of interactive web tools with visual and audio features significantly enhanced children’s engagement in the learning process; (2) thematic activities became more meaningful by connecting content with children’s daily experiences; (3) teachers benefited from the tools by designing more varied and developmentally appropriate learning activities; and (4) challenges arose from limited digital infrastructure and varying levels of teacher readiness in utilizing technology. These results highlight that integrating interactive web tools is a relevant and promising digital innovation to improve the quality of thematic learning in early childhood education, provided that continuous teacher training and adequate infrastructure are ensured